Optimization of prevention of dental diseases in pregnant women - N.G. Gadzhula; O.L. Cherepakha (Medičnì Perspektivi)
Effective prevention of dental diseases during pregnancy, as well as the correct tactics of a dentist and obstetrician-gynecologist is important factors in improving the level of dental health in pregnant women. The aim of research was to increase the effectiveness of the prevention of dental caries and periodontal diseases by introducing a complex of prophylactic and therapeutic measures in pregnant women. The implementation of the prophylaxis scheme is performed in 136 women aged 18-35 years. In the main group (70 women) prophylaxis was carried out using the complex of prophylactic and therapeutic measures developed by us, which includes: professional oral hygiene, oral health treatment, nutrition correction, prescribing the medicines of systemic and local action, training in proper teeth brushing, active sanitary and educational work. In the control group (66 women), the generally accepted prophylaxis scheme was used. Evaluation of the effectiveness of prophylactic and therapeutic measures was determined by indicators of caries incidence during pregnancy, reduction of caries, the dynamics of Papillary-Marginal-Attached Index and Papillary Bleeding Index. The effectiveness of the proposed algorithm of dental diseases prevention for pregnant women was confirmed by 3.45 times lower incidence of dental caries in women of the main group compared to the control group (0.44±0.06 versus 1.52±0.13 tooth, respectively); significant decrease (p<0.001) of Papillary-Marginal-Attached Index values (14.01±1.17 versus 49.25±1.86%), as well as bleeding indices (0.32±0.08 versus 1.82±0.13) and Green-Vermilion (0.89±0.08 versus 1.71±0.12 scores). Regular prophylactic and therapeutic examinations of pregnant women by a dentist, hygienic education and training of expectant mothers, active motivation of women to carry out individual oral hygiene with a constant monitoring of its implementation, correction of nutrition and mineral metabolism, influence on cariogenic and periodontal microbiota of the oral cavity, improvement of physiological enamel mineralization and increasing of hard tooth tissues resistance contributed to the reduction of caries incidence by 71.05±5.42% and the effectiveness of periodontal diseases treatment by 88.46±3.81% in the main group versus 36.84±5.94% in the control group (p<0.001).